2008
DOI: 10.1002/tox.20397
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological alterations in the liver of the sharptooth catfish Clarias gariepinus from polluted aquatic systems in South Africa

Abstract: There is a need for sensitive bio-monitoring tools in toxicant impact assessment to indicate the effect of toxicants on fish health in polluted aquatic ecosystems. Histopathological assessment of fish tissue allows for early warning signs of disease and detection of long-term injury in cells, tissues, or organs. The aim of this study was to assess the degree of histopathological alterations in the liver of C. gariepinus from two dams in an urban nature reserve, (Gauteng, South Africa). Two dams (Dam 1 and Dam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 32 publications
2
33
0
3
Order By: Relevance
“…Thus, congestion can be considered an indicator of stress in fish due to the presence of xenobiotic chemicals (Rezende et al, 2014). Marchand et al (2009) observed histopathological alterations in the liver of Clarias gariepinus from polluted aquatic systems in South Africa and found an increase in melanomacrophage centers, hepatocyte nuclear alterations, and necrosis of liver tissue. Necrosis is strongly associated with oxidative stress (Li et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, congestion can be considered an indicator of stress in fish due to the presence of xenobiotic chemicals (Rezende et al, 2014). Marchand et al (2009) observed histopathological alterations in the liver of Clarias gariepinus from polluted aquatic systems in South Africa and found an increase in melanomacrophage centers, hepatocyte nuclear alterations, and necrosis of liver tissue. Necrosis is strongly associated with oxidative stress (Li et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological assessment of fish tissues allows for early warning signs of disease and detection of long-term injury in cells, tissues, or organs (Marchand et al, 2009). The use of physiological and biochemical parameters as indicators of histopathological changes have been widely used as biomarkers in the health evaluation of animal organisms (El-Khayat et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to trace metals may cause histological changes in the liver and a histological investigation of exposed specimens may therefore produce meaningful results (van Dyk et al 2007;Marchand et al 2009). The present study demonstrates that the reference fish liver generally exhibited a normal architecture with a typical parenchymatous appearance and there were no pathological abnormalities.…”
Section: Histological Alterationsmentioning
confidence: 99%
“…Hinton & Laurén (1990), Bernet et al (1999), , Cazenave et al (2009) and Marchand et al (2009) consider that the different changes in many biochemical and morphological parameters of fish may be used as successful biomarkers for toxic effects of xenobiotics such as trace metals. Initial effects of metal pollution may be evident only at cellular or tissue levels before significant changes are identified in fish behavior or external appearance.…”
Section: Introductionmentioning
confidence: 99%